(untitled) - Chapman, Nigel (England, 2004)
Digital Multimedia is a core text for undergraduate and masters courses in multimedia. It combines a broad and deep account of technology with an inside understanding of multimedia content and its practical applications. Coverage begins with the nature of multimedia, including the cultural and social context, before examining hardware and software requirements for its creation and delivery. There are chapters devoted to each media type, detailing how it is represented in digital form and what demands are placed on computer systems. Later chapters cover design principles and accessibility, XML, SMIL and SVG, creating interaction through scripting and networking media. There are end-of-chapter exercises as well as suggestions for substantial projects and a detailed glossary of terms
Keywords: Digital media,Multimedia systems